New acylated flavonoid isolated from Thai bee pollen using molecular networking analysis and determination of its catechol-O-methyltransferase inhibitory activity. (February 2023) - Watanabe, Chie; Miyata, Ryo; Wakayama, Sachio; Kumazawa, Shigenori
Abstract: Bee pollen is an apicultural product comprising pollen collected by honeybees and it is consumed as a functional food by humans. In this study, we investigated the chemical profiles of Thai bee pollen using molecular networking analysis and observed one major cluster. This analysis also revealed that Thai bee pollen contains specific compounds. Using a molecular networking-guided method, we isolated several known compounds and one unique compound, which we identified as acylated flavonoid 8-methoxykaemferol-3- O -(2″- p -coumaroyl)-glucoside (1 ). We investigated the inhibitory activity of Thai bee pollen and the isolated compounds toward human catechol- O -methyltransferase, a key neurotransmitter involved in Parkinson's disease and depression. Compound 1 exhibited the highest activity of the tested compounds, with an IC50 value of 21 µM. Graphical Abstract: ga1 Highlights: Chemical profile of Thai bee pollen was revealed by molecular networking analysis. New acylated flavonoid 1 was isolated by molecular network-guided approach. Thai bee pollen and 1 exhibited remarkable COMT inhibitory activity.